15х – 3 = 10х + 122. –2х – 25 = –5х – 73. 4(5 – 2у) = 2(1 – у)4. 3у + 16 = 8у – 95. 4х + (11,8 – х) = 3,8 – 5х6. 3у + 2(2у – 3) = 8 – 7(у – 2)7. 2 – 5х = х + 148. 5(у – 7) = 3(у – 4) – 29 9. 11 – 5у = 12 – 6у

15х – 3 = 10х + 12 2. –2х – 25 = –5х – 7 3. 4(5 – 2у) = 2(1 – у) 4. 3у + 16 = 8у – 9 5. 4х + (11,8 – х) = 3,8 – 5х 6. 3у + 2(2у – 3) = 8 – 7(у – 2) 7. 2 – 5х = х + 14 8. 5(у – 7) = 3(у – 4) – 29 9. 11 – 5у = 12 – 6у
Гость
Ответ(ы) на вопрос:
Гость
15х-3=10х+12 15х-10х=12+3 5х=15 х=15:5 х=3 -2х-25=-5х-7 -2х+5х=-7+25 3х=18 х=18:3 х=6 4(5-2у)=2(1-у) 20-8у=2-2у -8у+2у=2-20 -6у=-18 у=-18 : (-6) у=3 3у+16=8у-9 3у-8у=-9-16 -5у=-25 у=-25 :(-5) у=5 4х+(11,8-х)=3,8-5х 4х+11,8-х=3,8-5х 4х-х+5х=3,8-11,8 8х=-8 х=-8 :8 х=-1 3у+2(2у-3)=8-7(у-2) 3у+4у-6=8-7у+14 3у+4у+7у=8+14+6 14у=28 у=28:14 у=2 2-5х=х+14 -5х-х=14-2 -6х=12 х=12:(-6) х=-2 5(у-7)=3(у-4)-29 5у-35=3у-12-29 5у-3у=-12-29+35 2у=-6 у=-6 :2 у=-3 11-5у=12-6у -5у+6у=12-11 у=1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы